MRI Assessment of Degeneration of the Tendon in Achilles Tendon Ruptures. (August 2019) - Bäcker, Henrik C.; Wong, Tony T.; Vosseller, J. Turner
Background: The extent of tendinosis along the entire tendon in Achilles tendon ruptures (ATRs) has not previously been assessed. MR images of acute ATRs were evaluated to assess this extent, even in areas distant from the rupture. Methods: Patients who had MR images for an ATR were reviewed. Each tendon was divided into a proximal, middle, and distal segment with the full tendon length defined as the length measured from the myotendinous junction to the insertion. The site of tendon rupture, presence of tendinosis and/or additional tearing, and largest anteroposterior (AP) diameter in the remaining segments were noted. In total, 45 MR iamges were included in our study. Results: The mean total tendon length was 9.93 cm, while the length from the insertion to the tear was 5.86 cm. Of the 45 ruptures, 20 (44.4%) were in the proximal third, 19 (42.2%) in the middle third, and 6 (13.3%) in the distal third. In all remaining segments where no ruptured tendon was observed, tendinosis was seen. Further, of the 90 segments of a tendon without rupture, 87 (96.7%) had an AP diameter greater than 6 mm. Of those 90 segments without rupture, 24 (26.7%) had a secondary partial-thickness tear in another third. Conclusion: Tendinosis is a known precursor of an ATR that in the current study was not limited to the area of rupture. The finding of extensive tendon degeneration may have implications for the optimal surgical treatment. Level of Evidence: Level IV, case series.